Effect of the FIFA 11+ on anterior cruciate ligament injury incidence rates in collegiate female football players over three consecutive seasons - Magoshi, H.; Hoshiba, T.; Tohyama, M.; Hirose, N.; Fukubayashi, T. (The Journal of Sports Medicine and Physical Fitness, 2026)
BACKGROUND: This non-randomized controlled trial aimed to investigate the preventive effects of the FIFA 11+ on anterior cruciate ligament (ACL) injury incidence rates in collegiate female football players in terms of intervention duration (one-season and over three consecutive seasons).